Pengaruh Promosi, Harga, dan Kualitas Produk terhadap Loyalitas Pelanggan pada Pembelian Teh Pucuk Harum - Zulvina Rahma Shofiudin; Lisa Sulistyawati (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This research aims to know how big is the influence of discount, price, and product quality on customer loyalty on the purchase of Teh Pucuk Harum. The population in this research was a consumer who have bought or consumed The Pucuk Harum. The sample in this research involved 100 respondents, namely East Java UPN students especially business administration study program. The results of the questionnaire distribution were measured using an ordinal scale. This type of research is descriptive research using the quantitative method. The sampling method in this research used non probability sampling using purposive sampling technique. The analytical method used multiple linear regression analysis through classical assumption testing, validity and reliability testing. The classical assumption test used the data normality test, multicollinearity test, and heteroscedasticity test. Multiple linear regression analysis method assessed through t test, and f test. The results of this research indicated that discount, price, and product quality had a positive and significant effect on customer loyalty on the purchase of Teh Pucuk Harum Keywords: Discount, Price, Product Quality, Customer Loyalty